A Multiple Streams Framework Approach to Access to Domestic Violence Services in an Indigenous Community - Hoare, Ismael (Violence against women, 2022)
This article focuses on access to domestic violence services within Belize. Using data from community asset mapping, interviews with key informants, and focus groups with community members, the multiple streams framework was used to identify potential areas for intervention to improve access and ameliorate the effects of family violence in Belize. Identified challenges to accessing limited domestic violence resources were mainly confidentiality concerns and mistrust. Existing laws and regulations, organizational structures, and policies and plans also influenced access. Women's groups, nongovernmental organizations, and the health department can play a crucial role in improving access to domestic violence services.